The Influence of Sarpras Management on the Quality of Graduates in SMPN in Awangpone District - Rismawati Basri; Baharuddin Baharuddin; Alwan Suban; Muh Wayong; Andi Ika Prasasti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the influence of facility and infrastructure management on the quality of graduates in public junior high schools. The main underlying problem is that researchers found low quality of graduates in several public junior high schools, which is suspected to be related to the suboptimal management of educational facilities and infrastructure. The research method used is quantitative with an ex post facto approach. The data collection technique was carried out by distributing questionnaires to 80 respondents consisting of principals, teachers, and educational staff in public junior high schools. Data analysis was conducted using a simple linear regression technique to test the influence of facility and infrastructure management on graduate quality. The results showed that facility and infrastructure management had a positive and significant effect on graduate quality with a coefficient of determination (R²) of 0.625. This means that facility and infrastructure management contributed 62.5% to improving graduate quality, while the rest was influenced by other factors. This finding confirms that the availability, maintenance, and optimal utilization of facilities and infrastructure can improve the quality of educational output. Therefore, facility and infrastructure management needs to be a primary concern for schools in an effort to continuously improve graduate quality.